The Unique Biogeochemical Signature of the Marine Diazotroph Trichodesmium - Nuester, Jochen; Vogt, Stefan; Newville, Matt; Kustka, Adam B.; Twining, Benjamin S. (Frontiers in Microbiology, 2012)
The elemental composition of phytoplankton can depart from canonical Redfield values under conditions of nutrient limitation or production (e.g., N fixation). Similarly, the trace metal metallome of phytoplankton may be expected to vary as a function of both ambient nutrient concentrations and the biochemical processes of the cell. Diazotrophs such as the colonial cyanobacteria Trichodesmium are likely to have unique metal signatures due to their cell physiology. We present metal (Fe, V, Zn, Ni, Mo, Mn, Cu, Cd) quotas for Trichodesmium collected from the Sargasso Sea which highlight the unique metallome of this organism. The element concentrations of bulk colonies and trichomes sections were analyzed by ICP-MS and synchrotron x-ray fluorescence, respectively. The cells were characterized by low P contents but enrichment in V, Fe, Mo, Ni, and Zn in comparison to other phytoplankton. Vanadium was the most abundant metal in Trichodesmium, and the V quota was up to fourfold higher than the corresponding Fe quota. The stoichiometry of 600C:101N:1P (mol mol−1) reflects P-limiting conditions. Iron and V were enriched in contiguous cells of 10 and 50% of Trichodesmium trichomes, respectively. The distribution of Ni differed from other elements, with the highest concentration in the transverse walls between attached cells. We hypothesize that the enrichments of V, Fe, Mo, and Ni are linked to the biochemical requirements for N fixation either directly through enrichment in the N-fixing enzyme nitrogenase or indirectly by the expression of enzymes responsible for the removal of reactive oxygen species. Unintentional uptake of V via P pathways may also be occurring. Overall, the cellular content of trace metals and macronutrients differs significantly from the (extended) Redfield ratio. The Trichodesmium metallome is an example of how physiology and environmental conditions can cause significant deviations from the idealized stoichiometry.